Pembuatan Sistem Informasi Evaluasi Pelayanan Publik (Sieva) Sekolah Dasar Negeri pada Kementerian Pendayagunaan Aparatur Negara dan Reformasi Birokrasi - Radian Betayunanda; Kodrat Iman Satoto; Eko Didik Widianto (Jurnal Teknologi dan Sistem Komputer, 2015)
Public Service is government responsiblity , increasing needs of the community from time to time must be met equitably. The public deserves to get a good public service, feasible and equitable. Every government officers perform their duties for the sake of public service improvement. In order to improve public services running properly and transparently then there should be monitoring from government. One of the government agencies responsible for the monitoring improvement of public service is Ministry of Administrative Reform and Bureaucratic Reform. Public Service Division of Ministry of Administrative Reform and Bureaucratic Reform. has a system to be modernized with the use of information technology and the Internet for the better public service, and equal to the maximum feasible. Public Service Division have a system of evaluation that has been carried out and directed to several sectors especially in the education sector of Public Elementary School, but the evaluation system has not been effective and efficient because the evaluation is still done manually by bringing officers to every school. Therefore, the system need to be connected with internet so evaluation can be done effectively, quickly and efficiently. Information System should web based and using PHP for programming language and integrated with PostgreSQL database. The information system is called SI-EVA SD (Public Service Evaluation Information System for Elemantary School).